Pollination of wild lady slipper orchids Cypripedium yunnanense and C. flavum (Orchidaceae) in south-west China: Why are there no hybrids? (Botanical Journal of the Linnean Society (January 2008) 156: 1 (51-64)) - Banziger H. (2014)
[No abstract available]